2014
DOI: 10.1002/elps.201400045
|View full text |Cite
|
Sign up to set email alerts
|

Diversity study of 12 X‐chromosomal STR loci in Hui ethnic from China

Abstract: X-chromosomal STRs (X-STRs) have been used as complements of autosomal STR application in recent years. In this work, we present population genetic data of 12 X-STRs including DXS101, DXS10159, DXS10162, DXS10164, DXS6789, DXS7133, DXS7423, DXS7424, DXS8378, DXS981, GATA165B12, and GATA31E08 loci in a sample of 231 unrelated healthy individuals from the Hui ethnic group in Ningxia Hui Autonomous Region, China. Allelic frequencies of the 12 X-STR loci and haplotypic frequencies of the reported linkage groups (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…However, autosomal STRs may not be effective in some deficiency paternity cases, such as the father–daughter testing that the DNA of mother is not available, and the full sisters or paternal sisters testing that the DNA of their biological father is not available. X‐chromosomal STRs were proved to be effective in these cases , because one of two X‐chromosomes of daughter is certainly inherited from her biological father and the sisters share the same paternal X‐chromosome. However, only several studies were reported with some available multiplex amplification systems, including Mentype® Argus X‐8 kit (Biotype AG, Dresden, Germany), Investigator Argus X‐12 (Qiagen, Hilden, Germany) and ZJGA‐X12 STR kit (AGCU ScienTech, Wuxi, Jiangsu, China) in the past .…”
Section: Introductionmentioning
confidence: 99%
“…However, autosomal STRs may not be effective in some deficiency paternity cases, such as the father–daughter testing that the DNA of mother is not available, and the full sisters or paternal sisters testing that the DNA of their biological father is not available. X‐chromosomal STRs were proved to be effective in these cases , because one of two X‐chromosomes of daughter is certainly inherited from her biological father and the sisters share the same paternal X‐chromosome. However, only several studies were reported with some available multiplex amplification systems, including Mentype® Argus X‐8 kit (Biotype AG, Dresden, Germany), Investigator Argus X‐12 (Qiagen, Hilden, Germany) and ZJGA‐X12 STR kit (AGCU ScienTech, Wuxi, Jiangsu, China) in the past .…”
Section: Introductionmentioning
confidence: 99%
“…Short tandem repeats (STRs) have become popular DNA markers in forensic DNA labs for more than 20 years and have been proved to possess several benefits, which make them especially suitable to identify victims, perpetrators, missing persons, and for kinship testing and population genetic analysis12345. However, there were some potential limitations of STRs in forensic applications because of its relatively high mutation rate, long amplicon size, and the deficiency in the analysis of highly degraded DNA samples and complex kinship cases.…”
mentioning
confidence: 99%
“…DXS8378-DXS10148-DXS10135, DXS7132-DXS10079-DXS10075-DXS10074, DXS10103-DXS10101-HPRTB and DXS10134-DXS7423 ( ) were classified as linkage groups 1, 2, 3 and 7, respectively. DXS6809-DXS6789 ( Pasino et al, 2011 ; Szibor et al, 2003a ) was specified as linkage group 4; DXS10159-DXS10162-DXS10164 ( Meng et al, 2014 ; Ye et al, 2014 ) as linkage group 5; and DXS7424-DXS101 ( Edelmann et al, 2002 ; Szibor et al, 2003a ) as linkage group 6. The haplotypic frequencies and haplotypic diversities of the seven linkage groups are shown in Table S3 .…”
Section: Resultsmentioning
confidence: 99%